2009
DOI: 10.1016/j.scitotenv.2009.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the non-protein thiol pool and production of dissolved gaseous mercury in the marine diatom Thalassiosira weissflogii under mercury exposure

Abstract: Two detoxification mechanisms working in the marine diatom Thalassiosira weissfloggii to cope with mercury toxicity were investigated. Initially, the effect of mercury on the intracellular pool of non-protein thiols was studied in exponentially growing cultures exposed to sub-toxic HgCl 2 concentrations. T. weissfloggii cells responded by synthesizing metalbinding peptides, named phytochelatins (PCs), besides increasing the intracellular pool of glutathione and γ-glutamylcysteine (γ-EC). Intracellular Hg and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 53 publications
1
40
0
1
Order By: Relevance
“…This was confirmed by the fact that HgGS 2 and HgPC 2 , as well as PC 4 , were observed when the fraction was determined using MALDI-TOF-MS (Figure 4(b)). Previous studies also showed that some water plants (Hydrilla verticillata and Vallisneria spiralis L. [17]), a microalga (Thalassiosira weissflogii [28]) as well as some terrestrial plants (Brassica napus [29] and Brassica chinensis L. [30]) can produce PCs under the exposure to Hg.…”
Section: Transformation Of Hg Inside P Tricornutummentioning
confidence: 93%
“…This was confirmed by the fact that HgGS 2 and HgPC 2 , as well as PC 4 , were observed when the fraction was determined using MALDI-TOF-MS (Figure 4(b)). Previous studies also showed that some water plants (Hydrilla verticillata and Vallisneria spiralis L. [17]), a microalga (Thalassiosira weissflogii [28]) as well as some terrestrial plants (Brassica napus [29] and Brassica chinensis L. [30]) can produce PCs under the exposure to Hg.…”
Section: Transformation Of Hg Inside P Tricornutummentioning
confidence: 93%
“…[44][45][46] However at lower Hg concentrations and longer exposure time, PCs do not seem to have a noticeable role in diatoms. [41] Therefore PCs role in Hg detoxification under environmentally relevant conditions remains to be confirmed.…”
Section: Mercury Intracellular Transformationsmentioning
confidence: 98%
“…[43] Reduction and demethylation of Hg are other intracellular transformations observed for both phytoplankton and macrophytes.Algal Hgreduction rates were shown to depend on exposure concentrations, but not on the light conditions. [44,45] The diatom T. weissflogii exposed to 5 nM Hg II produced comparable amount of Hg 0 in the light and in the dark conditions. [45] The mechanisms by which primary producers reduce Hg are still to be elucidated.…”
Section: Mercury Intracellular Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phytoplankton can produce antioxidant enzymes to scavenge reactive oxygen species, which are overproduced due to stress under Cd exposure, such as superoxide dismutase, catalase, and ascorbate peroxidase (Pinto et al 2003). Additionally, some species are able to synthesize glutathione (GSH) and other non-protein thiol peptides to reduce cytotoxicity as a result of exposure to Cd (Morelli and Pratesi 1997;Kawakami et al 2006;Morelli et al 2009). …”
mentioning
confidence: 99%